Numerical evaluations of hydrogen outgassing from cesium coated carbon fiber electrodes. (April 2022) - Sami, S.N.; Islam, R.; Portillo, S.; Schamiloglu, E.; Joshi, R.P.
Abstract: Outgassing remains a pertinent issue, especially for high power vacuum electronics, as it typically is the first stage of possible plasma formation, and can lead to effects such as breakdown, surface flashover, and pulse shortening in high power systems. Here, assessments of outgassing from composite cesium (Cs) coated carbon fibers which could be a preferred cathode material, are carried out based on molecular dynamics simulations. Our results obtained over a temperature range spanning 400 K–1000 K show hydrogen diffusion to be the slowest in carbon fibers, and highest in the Cs coating. This suggests that the addition of a Cs-coating, besides reducing work function, would speed up outgassing, and be useful in purging unwanted absorbed gases by pre-treatment involving initial surface heating. It has also been shown that outgassing can be a relatively fast process and to occur over sub-microsecond time scales, which is qualitatively in agreement with regards to the temporal span reported in measurements of hydrogen desorption related to rapid plasma formation observed in large-scale pulsed power machines. Highlights: Hydrogen outdiffusion in carbon fiber electrodes can be increased by cesium coating Cesium coating would help in purging unwanted gases via initial heat pre-treatment Cesium coating would also lower workfunction for stronger electron emission Outgassing can be achieved over sub-microsecond time scales Simulation results appear to be in agreement with data from Sandia National Laboratories